Skill Based Teacher Education in Blended Learning Scenarios - Ralf Schlöffel; Thomas Borchert (European Teacher Education Network, 2017)
Development, implementation and reflection of blended learning scenarios, have become established in both research and education (Mehl 2011). Results are evident for the different phases of teacher education. Imbedded in a design based research a blended learning scenario was developed in which students were enabled to video-record each other's teaching and interacting during school lessons and finally to cooperatively reflect those. Evaluation was realized with guided group interviews. Based on interferences when students reflected their own and fellow students' teaching, clear effects can be outlined. By dealing with their own and their fellow students' video material students gained new knowledge and competencies.